NILAI KEARIFAN LOKAL TRI HITA KARANA PADA MASYARAKAT ADAT KEPAON SEBAGAI WUJUD IMPLEMENTASI NILAI-NILAI PANCASILA - Qais Raihan; Matroni; Moh Ikmal (STKIP Subang, 2026)
This study examines the local wisdom values of Tri Hita Karana within the Kepaon Indigenous Community and their relevance as a manifestation of Pancasila values. Tri Hita Karana, a Balinese philosophical concept emphasizing harmonious relationships between humans and God (Parahyangan), among humans (Pawongan), and between humans and the natural environment (Palemahan), serves as a foundational principle guiding the social, spiritual, and environmental life of the Kepaon Adat community. In the context of Indonesia's national ideology, this local wisdom demonstrates a substantive alignment with the five principles of Pancasila, particularly in fostering religious devotion, social unity, and justice. This study employs a descriptive qualitative research method. Data were collected through in-depth interviews with Anak Agung Ketut Wirya, the Bendesa Adat (customary village head) of Kepaon, as the primary informant. Data analysis followed the Sugiyono interactive model comprising data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that Kepaon's indigenous community actively implements Tri Hita Karana through ritual maintenance of Kahyangan Tiga temples (Parahyangan), communal cooperation and interfaith tolerance with the local Muslim community (Pawongan), and periodic environmental cleanliness activities including mangrove conservation (Palemahan). These practices reflect the core values of Pancasila, particularly the first, second, third, and fifth principles. The community also faces modernization challenges such as land-use conversion, waste management issues, and rising criminality, to which they respond through adaptive customary strategies.